2020
DOI: 10.2147/ott.s253600
|View full text |Cite
|
Sign up to set email alerts
|

<p>Plasma Exosomal Long Noncoding RNA lnc-SLC2A12-10:1 as a Novel Diagnostic Biomarker for Gastric Cancer</p>

Abstract: Exosomes participate in cellular communications by transmitting active molecules, including long noncoding RNAs (lncRNAs) and are regarded as suitable candidates for disease diagnosis. This study aimed to identify gastric cancer (GC)-specific exosomal lncRNA and investigate the potential diagnostic value of plasma exosomal lncRNA in GC. Patients and Methods: Exosomes from the culture media (CM) of four GC cells (GCCs) and human gastric epithelial cells were isolated. Exosomal RNA was extracted, and lncRNA micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Serum exosomal miRNA profiles of steroid-induced osteonecrosis of the femoral head (SONFH) and hsa-miR-135b-5p may be a unique diagnostic biomarker for SONFH (131). Zheng et al found that the expression level of exosomal lnc-SLC2A12-10:1 was significantly correlated with tumor size, TNM stage, lymph node metastasis, and degree of differentiation, suggesting that exosomal lnc-SLC2A12-10:1 may be a potential noninvasive biomarker for the diagnosis and prognosis monitoring of gastric cancer (132). In summary, ncRNAs derived from exosomes are considered potential new biomarkers for various diseases, especially cancer, and can be easily detected in liquid biopsies.…”
Section: Exosomal Ncrna As a Specific Biomarker For Liquid Biopsymentioning
confidence: 99%
“…Serum exosomal miRNA profiles of steroid-induced osteonecrosis of the femoral head (SONFH) and hsa-miR-135b-5p may be a unique diagnostic biomarker for SONFH (131). Zheng et al found that the expression level of exosomal lnc-SLC2A12-10:1 was significantly correlated with tumor size, TNM stage, lymph node metastasis, and degree of differentiation, suggesting that exosomal lnc-SLC2A12-10:1 may be a potential noninvasive biomarker for the diagnosis and prognosis monitoring of gastric cancer (132). In summary, ncRNAs derived from exosomes are considered potential new biomarkers for various diseases, especially cancer, and can be easily detected in liquid biopsies.…”
Section: Exosomal Ncrna As a Specific Biomarker For Liquid Biopsymentioning
confidence: 99%
“…Their AUCs were 0.849 and 0.776, respectively, which were higher than the diagnostic efficiencies of traditional diagnostic markers (CEA, CA19-9, and CA72-4). Furthermore, their expression levels were significantly correlated with the TNM stage (173,174).…”
Section: Diagnostic and Prognostic Markersmentioning
confidence: 93%
“…The morphology and size distribution of the isolated exosomes were determined using transmission electron microscopy (TEM) and nanoparticle tracking analysis (NTA) following our previous description. 25 , 26 …”
Section: Methodsmentioning
confidence: 99%
“…The morphology and size distribution of the isolated exosomes were determined using transmission electron microscopy (TEM) and nanoparticle tracking analysis (NTA) following our previous description. 25,26 Cell Viability and Apoptosis Assay GC cells were seeded in a 96-well plate at 1500-3000 cells per well and incubated with doxorubicin for 48 h. Cell viability was detected with Cell Counting Kit-8 (Dojindo Laboratories, Japan). The optical density at 450 nm was measured on a multiwall plate reader (FLX800, Bio-TEK).…”
Section: Dovepressmentioning
confidence: 99%